2000
DOI: 10.1007/bf01268672
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic motion of an asymmetric gyrostat in the magnetic field of the earth

Abstract: Summary.The attitude motion of an asymmetric magnetic gyrostat satellite in a circular orbit subjected to both gravitational and magnetic forces of the earth is investigated by using the version of Melnikov's method developed for a two-degree of freedom Hamiltonian system with S 1 symmetry. For this purpose Deptrit's canonical variables are introduced to establish the Hamiltonian structure for this problem. It is found that the motion is chaotic in the sense of Smale's horseshoe under certain conditions. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Beletsky et al [9,10] discussed the chaotic motion of a magnetic spacecraft in circular polar orbit without damping and gravitational torque numerically. Cheng, Chen and Liu [11][12][13] studied the chaotic motion of a magnetic spacecraft in a circular orbit by using the Melnikov method and found that the onset of chaos is characterized by the intermittence as the increase of the magnetic torque. In present paper, the planar libration of a spacecraft in an arbitrary elliptic orbit under the action of gravitational and magnetic torque of the earth is treated.…”
Section: Introductionmentioning
confidence: 99%
“…Beletsky et al [9,10] discussed the chaotic motion of a magnetic spacecraft in circular polar orbit without damping and gravitational torque numerically. Cheng, Chen and Liu [11][12][13] studied the chaotic motion of a magnetic spacecraft in a circular orbit by using the Melnikov method and found that the onset of chaos is characterized by the intermittence as the increase of the magnetic torque. In present paper, the planar libration of a spacecraft in an arbitrary elliptic orbit under the action of gravitational and magnetic torque of the earth is treated.…”
Section: Introductionmentioning
confidence: 99%